The effect of polymer structure and interaction on paper strength - Zhang, Jin (My University, 2000)
Polymers are routinely used in paper making to enhance the strength of paper. The strength enhancing effect of polymers on paper is generally attributed to the increase in the fiber-fiber bond strength. This thesis focuses on the links between the structures and interactions of adsorbed polymers and the resulting strength of fiber-fiber bonds. Dextran was chosen as the model of strength enhancing polymers in this work. The molecular weight, charge density, and hydrophobicity of the dextrans were varied. Mixtures of dextran and hydrophobically modified dextrans were employed to investigate the role of adsorbed polymer compatibility in fiber-fiber bonding. Cationic dextran with different charge densities (0.161-0.488 meq/g) was prepared. Hydrophobically modified dextran was made by the reaction of dextran with straight chain saturated C3, C4 and C6 fatty acids. The incompatibility of dextran and hydrophobic dextran was evaluated by means of the biphase formation of an aqueous mixture of the two polymers. The adsorption behavior of dextrans on pulp fiber was measured. It was observed that the maximum amount of adsorption increased with a decrease in the molecular weight and charge density of the dextran. The strength of paper was evaluated using tensile strength and Scott bond tests. The strength enhancing effect of dextran was given as a function of molecular weight, charge density, hydrophobicity, and incompatibility with hydrophobic dextran. When fiber surface was saturated with dextran, it was found that the tensile strength of paper did not depend on the molecular weight of the dextran in the range investigated (77,000 to 2000,000). The charge density of the dextran affected the strength of paper by changing the maximum amount of dextran adsorbed on fibers. Introducing hydrophobic groups into dextran decreased the strength enhancing ability of dextran. The strength enhancing mechanism of dextran was proposed to be the formation of dextran intermolecular bonds between fibers. For the first time, the role of polymer incompatibility in determining the strength of paper was demonstrated in this work. It was found that the bond strength between fibers coated with two incompatible polymers was weaker than that obtained from the single polymer coated fibers. The Page equation, along with the model developed in this work, was applied to calculate the bond strength for each type of bonding.
Keywords: Chemical Engineering; Chemical Engineering